Russia and China in Central Asia: Cooperation or Partnership - Yryskeldiyeva, N. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2020)
Great powers as the US, Europe and China always have conflict due to their uncommon interests and they try to spread own influence over small countries and increase their power positions. This research investigates great power relationships as well as possibilities of cooperation and conflict between them. Rising power like China always worry great powers with its rapid development and influential position in Asia. Russia is also the country which has significant role in post-Soviet countries lives. And both China and Russia have had problematic relationship with western countries. As sanctions and troubled relationship between the West on one hand and Russia and China on the other hand appeared, the world tends to say that these countries will get closer to each other. After troubled relationship with the West, Russia and China want to increase influence in Central Asia. Central Asia has significant role due to its strategic location and natural resources deposits. Countries of Central Asia may become the focal point for both East and West with their energy potentials. This research tries to define potential role of Central Asian countries in great power relationships and how small and rising countries of Central Asia can take benefit from great powers involvement in their territory.
Keywords: Central Asia, great powers, cooperation of great powers, shared-neighborhood, geopolitics, great powers’ partnership, great powers’ issue, great powers’ energy need, small powers